SAVITRIBAI JYOTIRAO PHULE’S FIGHT FOR THE RIGHTS OF INDIAN WOMEN AND MARGINALIZED PEOPLE: A PIONEER INDIAN SOCIAL WORKER - Chand, Gian; Lal, Sohan; Lucy (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Savitribai Jyotirao Phule was one of the greatest pioneer Indian social reformers, educators, and poets in the 19th century. She played a crucial role in the education and empowerment of women, especially through her efforts in founding the first girls' school in Pune at Bhide Wada, along with her husband Jyotirao Phule. Savitribai worked tirelessly to improve the lives of child widows, fought against harmful practices like sati and child marriage, and advocated for widow remarriage. In addition, she was a strong supporter, as well advocate for the removal of caste and gender discrimination and campaigned against untouchability. The study is conducted to examine the role of Savitribai Phule as a social reformer and also to analyze Phule’s contribution to the development of women’s education & empowerment. This study adopts a qualitative approach, utilizing the qualitative content analysis technique to examine the educational and social contributions of Savitribai Phule with the application of descriptive-cum-analytical research design. Study has explored various research studies, books and other research work, which are based on primary sources of data. It is found that Phule viewed education as a powerful tool of liberation, something that could help oppressed and marginalized communities, particularly women and Socio-economically weaker sections, to break free from the societal shackles that kept them ignorant and subjugated. Her vision of education went beyond the traditional curriculum. She aimed to create a system that would foster gender sensitivity, intellectual criticality, and a socially reforming mindset. For Phule, education was not considered just about acquiring knowledge, but about enabling individuals to challenge entrenched social norms, particularly those related to gender discrimination and caste-based exclusion. It is concluded that lesson from the Savitribai Phule's journey; can be undertaken by the social work to advocate and protect the rights of the marginalized communities and women, in advancing comprehensive social justice and equality.